Antibacterial polysulfone membranes: the effect of eugenol and zinc oxide as additives - Harun, Zawati; Yusof, Khairul Nazri; Yunos, Muhamad Zaini; Shohur, Muhamad Fikri; Jamalludin, Mohd Riduan (Trans Tech Publications, 2016)
The purpose of this study was to investigate the influence of eugenol and zinc oxide on antibacterial properties of polysulfone membrane. Polysulfone membranes were prepared by a simple phase inversion technique with N-methyl-2-pyrrolidone (NMP) as solvent and polyethylene glycol as pore forming agent with zinc oxide and eugenol as additives. Membrane structure were characterized using scanning electron microscope (SEM) to observe the effect of both additives towards the formation of dense top layer and porous bottom layer of membrane. Disc diffusion test was conducted to evaluate the antibacterial performance against Escherichia coli (E.coli). SEM result showed the formation of thin top and bottom layers with more porous structure for hydrophilic zinc oxide particle, while dense top and bottom layers with slightly smaller porous network for eugenol addition. However, accumulations of particles were found for membrane with zinc oxide at higher concentration. The synergistic effect of combination zinc oxide and eugenol on antibacterial activity against E coli was found in this study. Besides that, the inhibition ring of membrane was improved 200% when both zinc oxide and eugenol were added in polysulfone membrane, Based on the findings, we can conclude that membrane with a combination of zinc oxide and eugenol has a huge potential membrane for bacterial removal.